Language Disorders of Elementary School Students in the Perspective of the Coastal Languages of Sibolga- Tapanuli Tengah - Tanjung, Tobi Bagustian; Rosmawaty, Rosmawaty (BIRCU, 2024)
Neuropsycholinguistics is a science that combines psychology, neurology and linguistics, and can be used to analyze language disorders, and is a combination of psycholinguistics and neurolinguistics. Language disorders in children occur due to brain development and are also due to the influence of learning language from other people and producing words that are sometimes pronounced in different ways. This research used a qualitative approach by collecting data through observation, interviews and recording on 3 students with language disorders at MIN 7 Tapanuli Tengah which were then analyzed using Neuropsycholinguistic theory by connecting it to the Coastal Languages of Sibolga- Tapanuli Tengah. Research found that the main cause of language disorders in 3 children could be identified through Neuropsycholinguistic theory, namely disrupted mental and brain development due to health conditions in the past which then had to be overcome through appropriate teaching methods and special attention to the child's psychological condition. The Coastal Languages of Sibolga- Tapanuli Tengah, which contains many words with changes, reductions and additions of phonemes from Indonesian, will disturb children with language disorders so they must receive special attention.